A Search for Causes of Rising Incidence of Differentiated Thyroid Cancer in Children and Adolescents after Chernobyl and Fukushima: Comparison of the Clinical Features and Their Relevance for Treatment and Prognosis - Drozd, Valentina (Multidisciplinary Digital Publishing Institute, 2022)
The incidence of differentiated thyroid cancer (DTC) is steadily increasing globally. Epidemiologists usually explain this global upsurge as the result of new diagnostic modalities, screening and overdiagnosis as well as results of lifestyle changes including obesity and comorbidity. However, there is evidence that there is a real increase of DTC incidence worldwide in all age groups. Here, we review studies on pediatric DTC after nuclear accidents in Belarus after Chernobyl and Japan after Fukushima as compared to cohorts without radiation exposure of those two countries. According to the Chernobyl data, radiation-induced DTC may be characterized by a lag time of 4-5 years until detection, a higher incidence in boys, in children of youngest age, extrathyroidal extension and distant metastases. Radiation doses to the thyroid were considerably lower by appr. two orders of magnitude in children and adolescents exposed to Fukushima as compared to Chernobyl. In DTC patients detected after Fukushima by population-based screening, most of those characteristics were not reported, which can be taken as proof against the hypothesis, that radiation is the (main) cause of those tumors. However, roughly 80% of the Fukushima cases presented with tumor stages higher than microcarcinomas pT1a and 80% with lymph node metastases pN1. Mortality rates in pediatric DTC patients are generally very low, even at higher tumor stages. However, those cases considered to be clinically relevant should be followed-up carefully after treatment because of the risk of recurrencies which is expected to be not negligible. Considering that thyroid doses from the Fukushima accident were quite small, it makes sense to assess the role of other environmental and lifestyle-related factors in thyroid carcinogenesis. Well-designed studies with assessment of radiation doses from medical procedures and exposure to confounders/modifiers from the environment as e.g., nitrate are required to quantify their combined effect on thyroid cancer risk.